Propuesta para la aplicación de la educomunicación, en el proceso de enseñanza y aprendizaje de noveno grado de educación básica de la Unidad Educativa Manuela Cañizares. - León Velasteguí, Joselyn Valeria (2017)
This academic article covers the problem of non-compliance with the proposal of the application of education in the teaching and learning process of the U.E. Manuela Cañizares according to the 2016 curriculum of the Ministry of Education from a theoretical and practical comparison. For this we apply interviews to the delegate of the educational unit, parent and student belonging to the U.E. Manuela Cañizares, participatory observations of the classes given to the students of 9th grade basic, in order to demonstrate why public education doesn't improve based on the research question: What characteristics have a proposal for the application of education, in The process of teaching and learning of the ninth grade of basic education of the Educational Unit Manuela Cañizares? Therefore, is that through the collection of information could be found shortcomings in fiscal education, Normative curriculum 2016 delivered by the Ministry Of Education to the EU Manuela Cañizares applying a traditional education leaving aside the communication and the TIC.